89x-3x=2x+14

Simple and best practice solution for 89x-3x=2x+14 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 89x-3x=2x+14 equation:


Simplifying
89x + -3x = 2x + 14

Combine like terms: 89x + -3x = 86x
86x = 2x + 14

Reorder the terms:
86x = 14 + 2x

Solving
86x = 14 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
86x + -2x = 14 + 2x + -2x

Combine like terms: 86x + -2x = 84x
84x = 14 + 2x + -2x

Combine like terms: 2x + -2x = 0
84x = 14 + 0
84x = 14

Divide each side by '84'.
x = 0.1666666667

Simplifying
x = 0.1666666667

See similar equations:

| -9x-5=-23 | | 5z-8=-5+6z | | (180-x)-3(90-x)=30 | | a+7/3=4 | | 5x+3*0=12 | | X^2-3x+16= | | x^2+3xy-5x-3y+y^2=0 | | 8x+9=9x-2x | | -5*(3^2-2)+(7*5+7)/6 | | -x+1.9=0.4+2x | | y=cx-dx | | x-0.8=8.39 | | 6=8x+10 | | 35+8x= | | 32t=-160 | | (x+8)/10=8/5+(x-2)/3 | | r-4r-3s+10s-3t+8t=0 | | 4-1/3a=10 | | 6(m-6)+4(3m+4)=17(m-2)-2 | | 26+4y-10=13y-12-2y | | -13=k-16 | | 12x^2-25x-11=-4 | | 2x-4=2x+8/3 | | graphy+2=-2(x+4) | | 6y=28+2y | | 2x-3=12x | | 6(6m-2)= | | y/4+5=-16 | | 6(2x-1)-2(2x)=6 | | 3-2y+3= | | p^2+12p+40=8 | | x/5-6=0 |

Equations solver categories